Robert Kennedy, in his own words the unpublished recollections of the Kennedy years - Kennedy, Robert F., 1925-1968; Guthman, Edwin O., 1919-2008.; Shulman, Jeffrey, 1951-. (Toronto ; New York Bantam, 1988)
Transcripts of interviews originally recorded in the mid-1960s for the John F. Kennedy Library
Published in cooperation with Twenty-First Century Books.
The Kennedy presidency, a chronology: pages 477-480
Includes index
Donated by M. Riley 1.28.16
Keywords: Kennedy, John F. (John Fitzgerald), 1917-1963.; Kennedy, Robert F., 1925-1968 -- Interviews; United States -- Politics and government -- 1961-1963.